The Statutes of the Youth Confraternity of the Purification of the Virgin Mary and of Saint Zenobius in Florence, 1444–ca. 1742 - Newbigin, Nerida (Confraternitas)

(untitled) (Iter Press, 2021)
The illuminated statutes of the Florentine youth confraternity of the Purificazione, now in the Lilly Library of the University of Indiana, were approved by Archbishop Antoninus in 1448. They set out the key concerns of the confraternity: good governance in order to foster moral and spiritual rectitude in the brethren, entry into and departure from the group, duties towards the sick, the dying and the dead, and proper forms of devotion on ordinary Sundays and feast days. The Purificazione statutes also prescribe the performance of a rappresentazione for the confraternity’s principal feast day. The statutes are translated here for the first time.